Involvement of a Response Regulator VdSsk1 in Stress Response, Melanin Biosynthesis and Full Virulence in Verticillium dahliae - Zheng, Jiayue; Tang, Chen; Deng, Chenglin; Wang, Yonglin (Frontiers in Microbiology, 2019)
Verticillium dahliae causes vascular wilt disease on over 200 plant species worldwide. This fungus forms melanized microsclerotia which help it to survive under adverse conditions and these structures are vital to the disease spread. Here, we identified and characterized a V. dahliae homolog to of the Saccharomyces cerevisiae Ssk1, a response regulator of the two-component system. Herein, we demonstrated that the VdSsk1 deletion strains were more sensitive to various stresses, including oxidative stress conferred by H2O2 and sodium nitroprusside dihydrate, while the mutants confered higher resistance to fungicides such as fludioxonil and iprodione. Furthermore, disruption of VdSsk1 resulted in significant downregulation of melanin biosynthesis-related genes but did not affect microsclerotial development. Phosphorylation of VdHog1 was not detected in the VdSsk1 deletion strains under the treatment of sorbitol, indicating that phosphorylation of VdHog1 is dependent on VdSsk1. Finally, we demonstrated that VdSsk1 is required for full virulence. Taken together, this study suggests that VdSsk1 modulates stress response, melanin biosynthesis and virulence of V. dahliae.